Calibrating different sounds for sound therapy: a general guide - Amirullah, Nur Afiqah; Rahmat, Sarah; Dzulkarnain, Ahmad Aidil Arafat; Maamor, Nashrah; Jamaludin, Mohd Khairil Azahar; Che Azemin, Mohd Zulfaezal (Malaysian Medical Association, 2022)
Introduction: Sound therapy is one of the complementary or alternative interventions for various populations. The intensity of the sounds for sound therapy needs to be properly calibrated to ensure their accuracy and effectiveness. This paper aims to provide a general guideline for calibrating sound files using free software, specifically Audacity®. Materials and Methods: Six sounds (broadband noise, rain, ocean, waterfall, Quranic chapters Al-Fatihah, and Yasin recitations) were calibrated at the intensity levels of 45, 50, 55, 60, 65, 70, 75, and 80dBA. The sounds were delivered through a pair of Sennheiser HD 280 Pro headphones connected to the Sound Blaster X-Fi Surround 5.1 Pro sound card. The long-term average of the sound pressure level over the time of recording (LAseq) was recorded using the 3M SoundPro Class 1 1/3 Octave RTA sound level meter (SLM). The desired intensity levels were obtained by making adjustments to the sound files via the Audacity® software. Results: All sound files were calibrated at the targeted levels as verified by the value of LAseq. Conclusions: Calibration of audio files can be done using a free/open-source software, as all six sound files were successfully calibrated at the targeted levels of 45, 50, 55, 60, 65, 70, 75, and 80dBA. The calibration steps provided in this paper can be easily applied by other researchers for similar purposes, with precautions when calibrating at low levels.